A direct formate microfluidic fuel cell with cotton thread-based electrodes. (16th October 2020) - Wang, Shaolong; Ye, Dingding; Liu, Zhenfei; Chen, Rong; Zhu, Xun; Zhang, Biao; Wu, Rui; Liao, Qiang
Abstract: A direct formate microfluidic fuel cell with cotton thread-based electrodes is proposed. The palladium catalyst is directly coated on cotton threads by repeated dipping method to prepare electrodes, which integrates the flow channel and electrode together and provides exposed active sites for enhancing the mass transfer on the anode and cathode. The aqueous anolyte and catholyte transport through cotton threads by capillary force with aid of gravity, eliminating the use of any external pump and facilitating the integration and miniaturization of the whole system. In the experiment, a three-flow channel structure is employed. The fuel is sodium formate and the oxidant is hydrogen peroxide. 1 M Na2 SO4 solution is introduced into the middle channel formed by cotton threads with no catalyst to alleviate the reactant crossover. Performance is evaluated under various catalyst loadings, fuel concentrations and differences in height between the inlet and outlet. Results show that the fuel cell produces an open circuit voltage (OCV) of 1.41 V. The maximum current density of 74.56 mA cm −2 and the peak power density of 24.75 mW cm −2 are yielded when the palladium loading is 1 mg cm −1 and the difference in height between the inlet and outlet is 7 cm, using 4 M HCOONa as fuel. Furthermore, the performance of the fuel cell increases first and then decreases with increasing the palladium loading. The same variation is observed with increasing the fuel concentration. However, the performance gradually increases with increasing the difference in height from 3 cm to 7 cm. The proposed microfluidic fuel cell with cotton thread-based electrodes shows enormous potential as a micro power source for portable devices. Highlights: A microfluidic fuel cell with cotton thread-based electrodes is proposed. Cotton threads coated with palladium catalyst form flow-through electrodes. Both the catalyst loading and operation condition affect flow rates of reactants. A peak power density of 24.75 mW cm −2 is delivered.